Influence of Different Acid Treatments on the Radiocarbon Content Spectrum of Sedimentary Organic Matter Determined by RPO/Accelerator Mass Spectrometry. Issue 2 (13th November 2018) - Bao, Rui; McNichol, Ann P; Hemingway, Jordon D; Lardie Gaylord, Mary C; Eglinton, Timothy I
ABSTRACT: In practice, obtaining radiocarbon ( 14 C) composition of organic matter (OM) in sediments requires first removing inorganic carbon (IC) by acid-treatment. Two common treatments are acid rinsing and fumigation. Resulting 14 C content obtained by different methods can differ, but underlying causes of these differences remain elusive. To assess the influence of different acid-treatments on 14 C content of sedimentary OM, we examine the variability in 14 C content for a range of marine and river sediments. By comparing results for unacidified and acidified sediments [HCl rinsing (Rinse HCl ) and HCl fumigation (Fume HCl )], we demonstrate that the two acid-treatments can affect 14 C content differentially. Our findings suggest that, for low-carbonate samples, Rinse HCl affects the Fm values due to loss of young labile organic carbon (OC). Fume HCl makes the Fm values for labile OC decrease, leaving the residual OC older. High-carbonate samples can lose relatively old organic components during Rinse HCl, causing the Fm values of remaining OC to increase. Fume HCl can remove thermally labile, usually young, OC and reduce the Fm values. We suggest three factors should be taken into account when using acid to remove carbonate from sediments: IC abundance, proportions of labile and refractory OC, and environmental matrix.